Flexible and Stretchable Carbon-Based Sensors and Actuators for Soft Robots - Xinyi Zhou; Wenhan Cao (Nanomaterials, 2023)
In recent years, the emergence of low-dimensional carbon-based materials, such as carbon dots, carbon nanotubes, and graphene, together with the advances in materials science, have greatly enriched the variety of flexible and stretchable electronic devices. Compared with conventional rigid devices, these soft robotic sensors and actuators exhibit remarkable advantages in terms of their biocompatibility, portability, power efficiency, and wearability, thus creating myriad possibilities of novel wearable and implantable tactile sensors, as well as micro-/nano-soft actuation systems. Interestingly, not only are carbon-based materials ideal constituents for photodetectors, gas, thermal, triboelectric sensors due to their geometry and extraordinary sensitivity to various external stimuli, but they also provide significantly more precise manipulation of the actuators than conventional centimeter-scale pneumatic and hydraulic robotic actuators, at a molecular level. In this review, we summarize recent progress on state-of-the-art flexible and stretchable carbon-based sensors and actuators that have creatively added to the development of biomedicine, nanoscience, materials science, as well as soft robotics. In the end, we propose the future potential of carbon-based materials for biomedical and soft robotic applications.